Conversion of coastal wetland to aquaculture ponds decreased N2O emission: Evidence from a multi-year field study. (1st December 2022) - Yang, Ping; Tang, Kam W.; Tong, Chuan; Lai, Derrick Y.F.; Zhang, Linhai; Lin, Xiao; Yang, Hong; Tan, Lishan; Zhang, Yifei; Hong, Yan; Tang, Chen; Lin, Yongxin
Highlights: Converting marsh to aquaculture ponds affected N2 O biogeochemical processes. N2 O production potential and N2 O emission were lower in converted ponds. Sediment N-cycling functional genes abundances were lower in converted ponds. Key drivers for N2 O emissions were N substrates, C:N, AOA genes and nirK genes. Abstract: Land reclamation is a major threat to the world's coastal wetlands, and it may influence the biogeochemical cycling of nitrogen in coastal regions. Conversion of coastal marshes into aquaculture ponds is common in the Asian Pacific region, but its impacts on the production and emission of nitrogen greenhouse gases remain poorly understood. In this study, we compared N2 O emission from a brackish marsh and converted shrimp aquaculture ponds in the Shanyutan wetland, the Min River Estuary in Southeast China over a three-year period. We also measured sediment and porewater properties, relevant functional gene abundance, sediment N2 O production potential and denitrification potential in the two habitats. Results indicated that the pond sediment had lower N-substrate availability, lower ammonia oxidation (AOA and comammox Nitrospira amoA ), nitrite reduction ( nirK and nirS ) and nitrous oxide reduction ( nosZ Ⅰ and nosZ Ⅱ) gene abundance and lower N2 O production and denitrification potentials than in marsh sediments. Consequently, N2 O emission fluxes from the aquaculture ponds (range 5.4–251.8 μg m –2 h –1 ) were significantly lower than those from the marsh (12.6–570.7 μg m –2 h –1 ). Overall, our results show that conversion from marsh to shrimp aquaculture ponds in the Shanyutan wetland may have diminished nutrient input from the catchment, impacted the N-cycling microbial community and lowered N2 O production capacity of the sediment, leading to lower N2 O emissions. Better post-harvesting management of pond water and sediment may further mitigate N2 O emissions caused by the aquaculture operation. Graphical abstract: Image, graphical abstract .